Sustainable Intensive Thermal Use of the Shallow Subsurface—A Critical View on the Status Quo. Issue 3 (14th May 2014) - Vienken, T.; Schelenz, S.; Rink, K.; Dietrich, P.
Abstract Thermal use of the shallow subsurface for heat generation, cooling, and thermal energy storage is increasingly gaining importance in reconsideration of future energy supplies. Shallow geothermal energy use is often promoted as being of little or no costs during operation, while simultaneously being environmentally friendly. Hence, the number of installed systems has rapidly risen over the last few decades, especially among newly built houses. While the carbon dioxide reduction potential of this method remains undoubted, concerns about sustainability and potential negative effects on the soil and groundwater due to an intensified use have been raised—even as far back as 25 years ago. Nevertheless, consistent regulation and management schemes for the intensified thermal use of the shallow subsurface are still missing—mainly due to a lack of system understanding and process knowledge. In the meantime, large geothermal applications, for example, residential neighborhoods that are entirely dependent up on shallow geothermal energy use or low enthalpy aquifer heat storage, have been developed throughout Europe. Potential negative effects on the soil and groundwater due to an intensive thermal use of the shallow subsurface as well as the extent of potential system interaction still remain unknown.